Genetic and environmental triggers of autoimmune thyroid diseases - Tomer, Yaron (Henry Stewart Talks, 2018)
Autoimmune thyroid diseases (AITD), Identification of AITD susceptibility genes, Iodine and AITD, MHC class II genes, CTLA-4, and CD40, Sequencing efforts, Environmental and genetic triggering factors of AITD, Genetic studies and etiology of AITD, Development of AITD